Operating characteristics of a high radius pre-swirl cooling system - Peng,Z; New,P; Long,CA; Childs,PRN (Hangkong Dongli Xuebao Journal of Aerospace Power, 2007)
An experimental investigation into pre-swirl effectiveness and receiver hole discharge coefficient characteristics for a high radius injection pre-swirl cooling systems was carried out on a physically representative experimental rig with a 450 mm diameter rotor. The receiver holes and pre-swirl nozzle were located at a radius of 181 mm and 180 mm respectively. The experimental work was mainly conducted at 5000-12000 r/min, 4 bar absolute pressure and 1.132 kg/s air supply. The maximum air supply temperature was 190°C. Pressure and temperature distributions in the pre-swirl system were examined with an emphasis on the velocity effectiveness of the pre-swirl system as a whole and on the discharge coefficients of the rotating 'receiver holes' in the rotor. The results showed that the velocity effectiveness increased with increasing swirl ratio resulting in reduced blade cooling flow temperature. Different seal flow configurations caused very different effectiveness at different speeds, but outflow through the inner and outer seals always gave the highest effectiveness compared other configurations. Increasing the seal flow rate reduced the effectiveness. For the coefficient of discharge, except for the low speed range, it increased with increase in swirl ratio for most speeds.